A simple case of upper limb venous thrombosis requiring anticoagulation? - Wallis, Adam (Clin Med (Lond), 2008)
In patients with arm swelling Paget-von Schroetter syndrome (PvSS) should be suspected and multidisciplinary treatment involving radiologists and surgeons considered.